Mathematic Perception In Whatsapp Group Interaction Teacher Participant PPG UHAMKA Year 2020 - Wahidin Wahidin (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This descriptive qualitative research aims to see the mathematical perceptions of the teachers participating in the 2020 PPG Daljab UHAMKA after being given the question "Look for three numbers whose total is 10 and the product of all three is an odd number" . A total of 57 teachers from 2 PPG classes were given questions through the WhatsApp groupwhich is directly responded by the teacher and the researcher responds until they get the right answer. Each of the teachers who got the correct answers and did not get the correct answers were interviewed to get information related to their perceptions. The results showed that the teacher had the perception that the 3 numbers must be whole numbers, so they never got the answer. Two teachers perceive that it cannot be integers, so they use fractions and decimals. No teacher has come up with an argument for why all three are integers. No teacher has ever performed the deduction process for the addition and multiplication of odd and even numbers. Even though this is an argument why this question cannot be answered